The Influence of Tourist Motivation on Revisit Intention through the Mediating Role of Destination Image: An Empirical Study of Inner Baduy Tribe Tourism - Regina Caeli Cahaya Tarsisty; Ratlan Pardede (Return : Study of Management, Economic and Bussines, 2025)
This study examines the influence of tourist motivation on revisit intention, with destination image as a mediating variable, in the context of a cultural destination with limited digital connectivity (Inner Baduy). Grounded in the Cognitive–Affective–Conative (CAC) framework, tourist motivation represents the cognitive domain, destination image the affective domain, and revisit intention the conative domain. A quantitative survey was conducted with 440 domestic visitors using purposive sampling, and data were analyzed using PLS-SEM. The findings reveal that destination image plays a crucial role in shaping revisit intention, while tourist motivation alone does not directly encourage repeat visits. Instead, the effect of motivation is channeled through the formation of a positive destination image, which significantly enhances the likelihood of returning. These results highlight the importance for destination managers to focus on managing visitor expectations and delivering emotionally engaging experiences that strengthen the destination’s image, thereby fostering long-term loyalty.